Analisis Spasio-Temporal Dampak Penambangan Pasir Terhadap Sosial Ekonomi Masyarakat Desa Kamelanta - Zulfanti Nur; Weka Widayati; Noor Husna Khairisa; La Ode Restele (Universitas Halu Oleo, 2024)
Sand mining in Kamelanta Village has been operating since 2008 and has an impact i the surrounding community. This research aims to: (1) find out the distribution of sand mining locations in Kamelanta village; and (2) determine the impact of sand mining on the socio-economic community. Data on the distribution of sand mining was obtained from field observations and data on the impact of sand mining was from interviews with 56 family cards. The method used in this research is a quantitative descriptive method. The method used in this research is a quantitative descriptive method. The results of this study include: (1) In 2008 there was only one sand mining location which was carried out in the traditional way using a shovel at low tide. Since 2018 mining activities have used suction machines and in 2023 there will be 39 sand mining locations spread along the coastline; (2) Sand mining in Kamelanta Village has positive and negative impacts. The positive impact is an increase in the economy with increased livelihoods and increased people's income. The negative impact is the damage to the seaweed cultivation location (especially Tobea Hamlet), so the seaweed farmers must do other work.